Determinations of red cell rediıced glutathione levels in konya merino sheep - Leyla KALAYCIOĞLU (Eurasian Journal of Veterinary Sciences)
The erythrocyte reduced glutathione levels in 91 Konya merino sheep and 10 rams of 3 years of age were measured. They were divided into two groups designed GSH high and GSH low according to their erytlirocyte GSH concentrations. The 31, 8% of sheep were the GSH low type and their mean GSH values was 29,76 mg/100 ml red cells and ranged between 10,14-49,78 mg/100 ml red cells, in rams the vaules of GSHh group ranged between 13,21-29,19 mg/100 ml red cells and the mean was 20,43 mg/100 ml red cells. The ranges and the mean vaules of GSHH groups both sheep and rams were 50-121,38 mg, mean 72,8 mg; 64,84-87,58 mg mean 79,20 mg/100 me red cells respectively.